Role of digitalization, digital competence, and parental support on performance of sports education in low-income college students - Li, Zongxi; Slavkova, Olena; Gao, Yong (Frontiers in Psychology, 2022)
Educational institutions have failed to achieve desired goals due to the lack of technology adoption, and this situation needs researchers’ emphasis. Hence, the current study examines the impact of digitalization and digital competencies among students on the educational performance of low-income college students in China. The article also investigates the moderating impact of parental support at the nexus of digitalization, digital competencies among students,and educational performance in low-income college students in China. The questionnaires were used by the researchers to gather the data from the selected respondents. The article has applied the smart-PLS to check the linkage among understudy constructs and test the hypotheses. The results revealed that digitalization and digital competencies among students positively link education performance. The results also exposed that parental support significantly moderates digitalization, digital competencies,and education performance in low-income college students in China. This article helps policymakers develop policies to improve educational performance using technology adoption.